Simulasi Model Kecelakaan Sepeda Motor Pada Ruas Jalan dengan Pendekatan GLM (Studi Kasus di Kabupaten Malang) - Sobri Abusini; Harnen Sulistio (Jurnal POINTER, 2010)
Abstract Models in mathematic is a media to help and that can be used for simplifying a reality, so that it will make an easier understanding on a complexs phenomenon. Transportation models is a model that can be used for explaining the transportation phenomenon with mathematic equation models. Based on the accident data, the number of traffic accident in Malang Residence is considered to be high. Therefore, in this study, the objective is to develop the Generalized Linear Model for motorcycle accident for Malang Residence in East Java Province. Using some statistical analysis it is found that the best-fit motorcycle accident model  is : Where : ﻿Acc = 0.009F0.703 exp(-0.334SW - 0.361G + 0.077S)Acc                = number of accident F             = Flow, pcu/hr SW         = shoulder width, m S             = speed, km/hr G            = Gradient (0,1) The model shows that the affecting factors are flow, shoulder width and speed, therefore local government should improve some related factor (flow, shoulder width, Gradient and speed) that can reduce the number of motorcycle accident at crossing road in Malang Residence. Keywords: Model kecelakaan sepeda motor, General Liniearized Model